2019
DOI: 10.1148/radiol.2019182561
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion CT to Assess Response to Neoadjuvant Chemotherapy and Radiation Therapy in Pancreatic Ductal Adenocarcinoma: Initial Experience

Abstract: ancreatic cancer is the fourth leading cause of cancerrelated mortality in the United States. In 2018, an estimated 55 440 people were diagnosed with pancreatic cancer, and 44 330 people died of it (1). Neoadjuvant chemotherapy and radiation therapy (CRT) is increasingly used to treat potentially resectable pancreatic ductal adenocarcinoma (PDA), especially for borderline resectable disease, as an alternative to surgery. CRT improves the rates of negativemargin resections and possibly treats early micrometasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
1
22
3
Order By: Relevance
“…Our findings argued against the results of previous studies that demonstrated the value of the DCE-CT (i.e., blood volume or K trans ) and DCE-MRI (i.e., K trans ) parameters in predicting the response of PDACs to gemcitabine-based chemoradiation therapy [9,12] or antiangiogenic therapy [36]. One possible reason for this difference may be the use of different therapeutic regimens in our and previous studies [9,12]. In addition, unlike our study, all previous studies evaluated only DCE-CT or MRI parameters, which may have not accounted for the confounding effects of other clinical and imaging factors on tumor response.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings argued against the results of previous studies that demonstrated the value of the DCE-CT (i.e., blood volume or K trans ) and DCE-MRI (i.e., K trans ) parameters in predicting the response of PDACs to gemcitabine-based chemoradiation therapy [9,12] or antiangiogenic therapy [36]. One possible reason for this difference may be the use of different therapeutic regimens in our and previous studies [9,12]. In addition, unlike our study, all previous studies evaluated only DCE-CT or MRI parameters, which may have not accounted for the confounding effects of other clinical and imaging factors on tumor response.…”
Section: Discussioncontrasting
confidence: 99%
“…None of the DCE-MRI parameters evaluated in our study showed significant association with tumor response in multivariable analysis, though model-free iAUC and peak enhancement showed significance in the univariable analysis. Our findings argued against the results of previous studies that demonstrated the value of the DCE-CT (i.e., blood volume or K trans ) and DCE-MRI (i.e., K trans ) parameters in predicting the response of PDACs to gemcitabine-based chemoradiation therapy [9,12] or antiangiogenic therapy [36]. One possible reason for this difference may be the use of different therapeutic regimens in our and previous studies [9,12].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In 15 out of 21 studies, BF was measured in both PDAC and non-tumorous pancreatic parenchyma, including a total of 519 patients. In all these studies, mean blood flow was significantly lower in tumor tissue compared to pancreatic parenchyma outside the tumor or in healthy pancreatic tissue in a control group [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Mean BF ranged from 17 to 60 mL/100 g/min for PDAC and 71-164 mL/100 g/min for pancreatic parenchyma.…”
Section: Diagnosismentioning
confidence: 93%
“…The accumulation of extracellular matrix, including collagen, fibronectin, proteoglycan, and hyaluronic acid, can induce the formation of rigid extracellular matrix to compress blood vessels, leading to perfusion damage and ultimately hindering the transmission of anti-cancer drugs to the tumor cells[ 58 ] (Figure 3 ). Based on the above theoretical assumptions, Hamdy et al [ 59 ] investigated the value of perfusion CT in predicting the response of PDAC to neoadjuvant chemotherapy and radiation therapy. The results showed that participants who responded to NAT had higher baseline blood flow than those who did not respond (median, 44 mL/100 g/min vs 28 mL/100 g/min, respectively).…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%